Learning to read the South African 1:50 000 topographic map: the development of a self-instruction method - Innes, Lorraine M. (My University, 2014)
The place of topographic map reading in geography education is discussed with particular reference to South Africa. Theories of literacy acquisition and geographic and spatial concept development are related to the teaching of map reading. The extent of and reasons for poor pupil performance in mapwork as well as its consequences are examined. Using outcomes based learning principles the task of reading the 1:50 000 topographic map is analysed, the skills required to perform the sub-tasks of recognition, identification and comprehension are identified and a method is developed to sequence the teaching of these tasks. Programmed instruction design is investigated and self-instruction materials for reading the South African topographic map are developed. Results of a pilot test conducted when the programme was in a formative stage guided the final layout of the materials. A teaching kit comprising 52 work cards and corresponding answer cards and a pupils' answer and record booklet was used by learners in grade nine during a classroom trial and the results are reported. The use of the self-instruction method improved the map reading performance of this small sample population of adolescents, improvements to the prototype and further testing are recommended.
Thesis (M.Ed.)--University of the Witwatersrand, Faculty of Education, 1998.